Coronary arteries anomalous aortic origin on a computed tomography angiography population: prevalence, characteristics and clinical impact - Amado, José (2017)
Anomalous aortic origin of coronary arteries (AAOCA) is one of the most frequent causes of cardiovascular sudden death among the young population. We aimed to determine the prevalence and anatomic characteristics of AAOCA in a population referred to computed tomography angiography (CTA) and to describe the clinical prognosis of these findings at middle term follow-up. From a total of 3539 CTA, 53 were found to have AAOCA. This population was compared to an age and gender matched control group (n = 106) from the same CTA list. A telephone follow-up to determine cardiac events was conducted, with a mean follow-up of 45.9 +/- 28.2 months. Prevalence of AAOCA was 1.5 %. The most common AAOCA was an origin of the right coronary artery (RCA) from the left coronary sinus, followed by an origin of the left circumflex artery (LCX) arising from the right coronary sinus. All patients with an anomalous origin of the RCA had an interarterial course. Four additional patients were found to have an interarterial course: 1 with an anomalous origin of LCX and 3 with an anomalous origin of the left main coronary artery (LMCA). At follow-up there were 33 (21.2 %) cardiac events, 9 (17.6 %) on the AAOCA group and 24 (22.9 %) on the control group (p = 0.46). Cardiac events and cardiovascular deaths were not related to any particular AAOCA or to interarterial courses. Among an adult population referred to CTA, AAOCA were not related with worse middle term prognosis when compared to an age- and gender- matched population.